THE SPEECH STYLE OF STUDENTS IN CLASSROOM INTERACTION OF ARABIC CLASSES ON PONDOK MODERN DARUSSALAM GONTOR 1 PONOROGO - LESTARI, CHARIS WAHYU (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: speech style, conversation, student, teacher.While most people are born with thephysical ability to talk, not all can communicate well unless they make specialefforts to develop and refine this skill further. This study was aimed to answer three problems of study. They are (1) what arethe speech styles used by the student while having conversation with his friend and his teacher in Arabic class on Pondok Modern Darussalam Gontor 1 Ponorogo (2)what the style occurs dominantly used by the student while having conversation with his friend and his teacher, and (3) what are the possible factors causing the uses of speech style when they communicate with the teacher and their friends. In this study, the researcher used the theory from Ryding (2005) about speech styles and Holmes (1992) about factors which influence the speech style.In this study, the researcher used descriptive qualitative approach because the researcher more focused on the explanation and description. The data of this studywere 30 conversations between student and student, and student and the teacher ofhigh, middle and low level class in Arabic class. In analyzing the data, the researcherdid the process of style identification and explanation about the style and the possiblefactors of using certain style.The result shows that while having conversation with the teacher, all students in high level class used formal style, in middle class almost all of the student used formal style, and in low class level, half of the student used formal style. While having conversation with his friend, almost all student in high, middle and low level class used the combination of formal and informal style. In addition, there were threepossible factors influencing the uses of speech style. Those factors were theparticipant (social status), setting and topic, but there were also some conversations which were not influenced by those three factors which could be caused by the lack of competence.From this study, the researcher suggest the next researcher analyze the speechstyle using another theory such as from Chaika, Holmes, Keraf and etc. The researcher also suggests future researchers analyze the function of speech style indaily conversation